KAJIAN FORMULASI NUTRISI AB MIX DAN VARIETAS TERHADAP HASIL CABAI KERITING (Capsicum annum L.) SECARA HIDROPONIK - Ali, Fahri; Yeni, Yeni; Rahhutami, Ratih; Kartina, Raida; Tiara, Dede (JURNAL AGROTROPIKA, 2025)
The problem faced by hydroponic farmers in cultivating chili peppers is the lack of an optimal AB Mix nutrient formula that can be synthesized independently using chemical fertilizers readily available in agricultural supply store. This study aims to evaluate the effects of AB Mix nutrient formulation and variety on yield of curly chili peppers (Capsicum annuum L.) in hydroponic system. The experimental design was a Randomized Block Design (RBD) in 2-factor split-plot arrangement with three replications. The main plots consisted of four nutrient formulations. The subplots consisted of plant varieties, which included the Lado Juara F1 variety, the Joker genotype, and Lolay genotype. The result of the study showed that increasin of the concentration of the AB Mix nutrient formulation from N1 to N2 enhanced the number of fruits and the fruit weight per plant, both in the Lado Juara, Joker, and Lolay varieties. However, further increases the concentration of the AB Mix nutrienr formulation from N2 to N3 and N4 decreased the number of fruits and the fruit weight per plant in any of varieties. The use of the Lado Juara variety resulted in higher numbers of fruits and fruit weight per plant compared to the Joker and Lolay genotypes across all AB Mix nutrient formulations with a drip irrigation hydroponic system. Key words: Chili, formulation, hydroponic, nutrition, variety